HUBUNGAN USIA DENGAN CERVICAL INFLAMMATION PADA WANITA USIA SUBUR - Nuke Devi Indrawati; Dewi Puspitaningrum; Indri Astuti Purwanti (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Background: Cervical inflammation is an early stage of cervical cancer, the most cancer that attacks the female reproductive organs in Indonesia. If cervical inflammation can be prevented earlier, the chances of cervical cancer can be significantly reduced (long-term). Research Objectives: This study analyzed the age relationship with cervical inflammation in Kelurahan Kedungmundu Semarang City. Type of research with analytical research. Methods: Univariate analysis with frequency distribution, bivariate analysis with chi square. The number of samples of 40 women participants screening IVA test screening. Result of the research: Total of 40 respondents majority of middle adult age that is 22 woman (55%), majority did not have cervical inflammation and healthy reproductive health equal to 33 woman ((82,5%), no significant relation between age with cervical inflammation (p value = 0,505) Conclusion: there is no significant correlation between age with incidence rate of cervical inflammation.Keywords: age, cervical inflammation